The Effects of Physical and Non-physical Investments of Government Expenditure in Education and Health Sectors on Human Development Index in Pekanbaru City - Muhammad Akbar Fatria; Harlen Harlen; Deny Setiawan (Indonesian Journal of Economics, Social, and Humanities, 2020)
In this current globalization era, human resources investment is necessary for each country to improve the index of human development and economic growth, many countries have succeeded in economic growth by relying on human resources despite not having abundant natural resources. However, the success of resource investment is also strongly influenced by the availability of supporting facilities and infrastructure. Based on data of physical and non-physical investments of government expenditure in education and health sectors from 2007-2017, shows a positive trend with relatively increasing value. Meanwhile, based on data of human development index progress in Pekanbaru city in recent years showed a relatively declining value. This contradicts the theory of endogenous romer which explained that when the government or private sectors invest in human resources, it will encourage the improvement of human resources quality that reflects the progress of human development index. This study uses secondary data, namely government physical and non-physical expenditure data in the field of education and health in Pekanbaru City on Regional Budget in 2010-2017. The independent variable is government physical and non-physical expenditure in education and health sectors. While the dependent variable is the Human Development Index. The analysis method used is OLS (Ordinary Least Square) method where the data used are analyzed quantitatively using statistical analysis, namely multiple linear regression equations. Based on the results of research, government physical expenditure in education and government non-physical expenditure in the health sector does not significantly influence the human development index in Pekanbaru City. While government non-physical expenditure in education and government physical expenditure in health significantly affect the human development index in Pekanbaru City. Furthermore, for physical investment where in this research is the government physical expenditure in education and health sectors simultaneously has a significant effect on the human development index in Pekanbaru City. Whereas for non-physical investment where in this study is government non-physical expenditure in education and health sectors simultaneously has a significant effect on the human development index in Pekanbaru City.